A Universal Plug-and-Display Vaccine Carrier Based on HBsAg VLP to Maximize Effective Antibody Response - Marini, Arianna; Zhou, Yu; Li, Yuanyuan; Taylor, Iona J.; Leneghan, Darren B.; Jin, Jing; Zaric, Marija; Mekhaiel, David; Long, Carole A.; Miura, Kazutoyo; Biswas, Sumi (Frontiers in Immunology, 2019)
Development of effective malaria vaccines requires delivery platforms to enhance the immunogenicity and efficacy of the target antigens. This is particularly challenging for transmission-blocking malaria vaccines (TBVs), and specifically for those based on the Pfs25 antigen, that need to elicit very high antibody titers to stop the parasite development in the mosquito host and its transmission. Presenting antigens to the immune system on virus-like particles (VLPs) is an efficient way to improve the quantity and quality of the immune response generated. Here we introduce for the first time a new VLP vaccine platform, based on the well-established hepatitis B surface antigen (HBsAg) fused to the SpyCatcher protein, so that the antigen of interest, linked to the SpyTag peptide, can be easily displayed on it (Plug-and-Display technology). As little as 10% of the SpyCatcher::HBsAg VLPs decorated with Pfs25::SpyTag (molar ratio) induces a higher antibody response and transmission-reducing activity in mice compared to the soluble protein, with 50 and 90% of the VLP coupled to the antigen further enhancing the response. Importantly, using this carrier that is a vaccine antigen itself could be beneficial, as we show that anti-HBsAg IgG antibodies are induced without interfering with the Pfs25-specific immune response generated. Furthermore, pre-existing anti-HBsAg immunity does not affect the antigen-specific response to Pfs25::SpyTag-SpyCatcher::HBsAg, suggesting that these VLPs can have a broad use as a vaccine platform.